2023
DOI: 10.1002/ana.26775
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Fat Depletion and Prognosis of Amyotrophic Lateral Sclerosis: CT‐Based Body Composition Analysis

Seok‐Jin Choi,
Soon Ho Yoon,
Jung‐Joon Sung
et al.

Abstract: ObjectiveTo investigate the prognostic value of adipopenia and sarcopenia in patients with amyotrophic lateral sclerosis (ALS).MethodsConsecutive ALS patients with abdominal CT were retrospectively identified at a single tertiary hospital between January 2010 and July 2021. Deep learning‐based volumetric CT body composition analysis software was used to obtain abdominal waist fat volume, fat attenuation, and skeletal muscle area at the L3 level, then normalized to the fat volume index (FVI) and skeletal muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Energy deposits are very important in patients with ALS; in fact, low fat mass measured by computed tomography (CT) is an independent poor prognostic factor for survival [27]. Another study by Lee et al showed that a low baseline percentage of body fat correlated with a decline in quality-of-life tests (r = 0.72) [28].…”
Section: Discussionmentioning
confidence: 99%
“…Energy deposits are very important in patients with ALS; in fact, low fat mass measured by computed tomography (CT) is an independent poor prognostic factor for survival [27]. Another study by Lee et al showed that a low baseline percentage of body fat correlated with a decline in quality-of-life tests (r = 0.72) [28].…”
Section: Discussionmentioning
confidence: 99%